Unlocking Reading Comprehension through Flashcards: An Experimental Study - Junia Bella Safitri; Testiana Deni Wijayatiningsih; Riana Eka Budiastuti (English Language Education Department, Universitas Majalengka, 2026)
Many students in one private junior high school in Central Java experienced difficulties in reading comprehension, which adversely affected their academic performance. Preliminary observations indicated that only approximately 40% of students demonstrated adequate comprehension skills. This study aimed to examine the effect of flashcard-based instruction in enhancing students’ reading comprehension. A quasi-experimental pretest–posttest design was employed, involving two groups of eighth-grade students: an experimental group receiving flashcard-based instruction and a control group receiving conventional teaching, with 24 students in each group. Data were collected through reading comprehension tests and a structured questionnaire. The findings revealed that the experimental group obtained a higher mean posttest score (M = 81.66) compared to the control group. However, the Mann–Whitney U test indicated that the difference between the groups was not statistically significant (p > .05). Despite the absence of statistical significance, the experimental group consistently demonstrated higher performance trends. Furthermore, questionnaire responses showed overwhelmingly positive student perceptions, highlighting the practicality, engagement, and motivational benefits of flashcards. These findings suggest that flashcard-based instruction has pedagogical value in supporting reading comprehension and learner engagement in private junior high school contexts.